Quality of Life after Suture Repair for Incisional Hernia: Long-Term Postoperative and Retrospective Preoperative Evaluations - den Hartog, D.; Dur, A. H. M.; Tuinebreijer, W. E.; Kreis, R. W. (Calitatea Vieții, 2009)
Purpose: The aim of this observational study was to examine postoperative and retrospective preoperative evaluations of multiple dimensions of patient quality of life after a threelayered closure repair for incisional hernia. Methods: After suture repair of an incisional hernia (mean follow-up of 4.6 years), 72 patients (32 female, 40 male, mean age 63.6 years) completed the SF-36 Health Survey Questionnaire to evaluate their current postoperative as well as their past preoperative quality of life. Results: All domains improved significantly after the operation. Relative to age-matched controls, the preoperative quality of life was evaluated negatively in seven domains, while the postoperative quality of life was evaluated negatively for only two domains. Conclusions: In this study, patients retrospectively evaluated their physical and mental health as poor before an incisional hernia repair. After the operation, patient quality of life improved, but the perceived quality of life did not completely normalize. Further prospective studies will be useful to examine the quality of life before and after ventral hernia repairs.